Computational hydrodynamic simulations for an underwater axisymmetric hemisphere-cylinder hull-form at incidence - Zahir, Salimuddin (Journal of Naval Architecture and Marine Engineering, 2014)
This contribution presents a computational simulation for a generic hull shape with attached short pin-protuberance for its hydrodynamic characteristics. This work is a part of a large framework of numerical simulation and experimentation carried out for blunted head-forms of hemispheric shapes for determination of aero-hydrodynamic coefficients and static stability features. Results are presented for a clean hull-form and with the pin-protuberance, as static axial and circumferential pressure distribution on the surface, calculated at a fixed velocity and at different angle of attacks, under non-cavitating depth and velocity. It is shown that a suitably located short lateral pin has an adequate effectiveness to control pitch maneuver of an underwater hemisphere-cylinder hull-form. In view of that, a suitable pin-height adjustment commensurate to pitch attitude trajectory corrections is a workable idea, and the concept has potential of effective pitch attitude control of the hemisphere-cylinder hull-form. DOI: http://dx.doi.org/10.3329/jname.v11i1.16725